Peran Desain Interior dalam Menciptakan Kenyamanan di Perpustakaan KPw Bank Indonesia (BI) Lampung - Intan Nilam Sari; Aghesna Rahmatika Kesuma; Rahmat Iqbal (Universitas Sebelas Maret Library, 2026)
Interior design is the planning and design of a building's interior spaces. The comfort of a space is an important factor that shapes library users' perceptions and experiences. This comfort can be realized through aspects of interior design. Therefore, the role of interior design in providing comfort, beauty, and functionality of spaces needs special attention so that the library remains relevant to the needs of modern society. This study aims to determine effective interior design strategies in creating comfort for library users at the KPw Bank Indonesia (BI) Lampung Library. The method used is a descriptive qualitative method, with data collected through structured interviews. The researcher tests the data's validity using triangulation to enhance its credibility and validity regarding the role of interior design in creating comfort at the KPw Bank Indonesia (BI) Lampung Library, through a combination of interviews, observations, and documentation. The research informants consist of librarians and library users selected through purposive sampling. The research results indicate that the comfort of library users at the KPw Bank Indonesia (BI) Lampung Library is influenced by several main aspects: color, spatial arrangement, and the facility. Optimal physical conditions, such as adequate natural lighting and a stable room temperature, have been proven to create a calm atmosphere. The right choice of colors can create visual comfort and enhance concentration, while a functional spatial arrangement facilitates user activities.